2003
DOI: 10.1046/j.1445-2197.2003.t01-1-02633.x
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical justification of Belghiti's ‘liver hanging manoeuvre’ in right hepatectomy with anterior approach

Abstract: The key to the liver hanging manoeuvre is to develop the retrohepatic tunnel. However, our study showed that it is not absolutely avascular. During the blind dissection, there is a chance of damaging a retrohepatic vein. This may result in troublesome haemorrhage within the confines of the tunnel. Video-assisted dissection of this region may help in visualisation, and hence control, in order to avoid bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 3 publications
1
32
1
Order By: Relevance
“…The avascular ''tunnel'' contains, on average, 3.7 SHVs which are relatively small (between 0.2 and 0.3 cm in diameter). Compared to other authors' reports [10][11][12][13], the number of SHVs in our group was smaller. Still, a special attention must be paid to the dissection of retrohepatic space; specifically, if the surgeon's assistant ignorantly rotates the right liver and tears SHVs or if the surgeon accidentally pierces RHICV, copious bleeding or air embolism will spontaneously occur.…”
Section: Discussioncontrasting
confidence: 78%
“…The avascular ''tunnel'' contains, on average, 3.7 SHVs which are relatively small (between 0.2 and 0.3 cm in diameter). Compared to other authors' reports [10][11][12][13], the number of SHVs in our group was smaller. Still, a special attention must be paid to the dissection of retrohepatic space; specifically, if the surgeon's assistant ignorantly rotates the right liver and tears SHVs or if the surgeon accidentally pierces RHICV, copious bleeding or air embolism will spontaneously occur.…”
Section: Discussioncontrasting
confidence: 78%
“…The IVC phase was timed in order to enable a stenotic IVC to fill with contrast medium. [13] Images were formatted in the axial, sagittal, and coronal planes. MRI with a dynamic enhanced angiography sequence was performed on a 1.5 Tesla or 3.0 Tesla Signa (HDxt 3.0T, General Electronic, USA).…”
Section: Methodsmentioning
confidence: 99%
“…However, right hepatectomy can be performed safely by combining the hanging maneuver with an anterior approach. 4 A straight-down transection along the principal plane between the right and left lobes provides the smallest Meng et al 3 suggested that the surgeon visualize the tunnel by pointing the laparoscope cranially from the infrahepatic region. However, we found that the abdominal wound limits the application of a rigid straight laparoscope, making handling in the narrow tunnel awkward.…”
Section: Discussionmentioning
confidence: 99%